Communication-efficient implementation of join in sensor networks - Chowdhary, Vishal; Gupta, Himanshu (International Conference on Database Systems for Advanced Applications, 2005)
A sensor network is a wireless ad hoc network of resource-constrained sensor nodes. In this article, we address the problem of communication-efficient implementation of the SQL “join” operator in sensor networks. We design an optimal join-implementation algorithm that provably incurs minimum communication cost under certain reasonable assumptions. In addition, we design a much faster suboptimal heuristic that empirically delivers a near-optimal solution. We evaluate the performance of our designed algorithms through extensive simulations.